Knockdown of lectin-like oxidized low-density lipoprotein-1 ameliorates alcoholic cardiomyopathy via inactivating the p38 mitogen-activated protein kinase pathway. Issue 4 (1st April 2022) - Zhang, Yifan; Zhang, Ruiqi; Lu, Lan; Zhou, Na; Lv, Xiaoyan; Wang, Xin; Feng, Zhanbin
ABSTRACT: LOX-1 triggers myocardial fibrosis, but its roles and mechanisms in alcoholic cardiomyopathy and the involvement of the downstream signaling pathways had not been fully reported. We planned to explore how LOX-1 facilitated myocardial fibrosis in alcoholic cardiomyopathy. The in vitro and in vivo alcoholic cardiomyopathy model was established by alcohol treatment to rats' cardiac fibroblasts and rats, respectively. Masson staining was conducted to observe the collagen deposition and the IHC assay was executed to evaluate the contents of collagen I and III in vitro and in vivo. The cardiac tissues were also observed under TEM and the cardiac function of rats was evaluated using UCG. The expression levels of LOX-1 and P38MAPK in cardiac fibroblasts and tissues at both mRNA and protein levels were analyzed by RT-qPCR and western blot, respectively. Alcohol treatment could trigger collagen deposition, cell hypertrophy, fibrotic changes and increased the expression levels of LOX-1 and P38MAPK both in vivo and in vitro. It also deteriorated the cardiac function of rats in vivo. Overexpression of LOX-1 in vitro could aggravate the fibrotic changes while knockdown of LOX-1 ameliorated the fibrotic effects of alcohol treatment both in vitro and in vivo such as reduction of collagen deposition, relief of cell hypertrophy and inactivation of the P38MAPK signaling pathway. We concluded that knockdown of LOX-1 exerted anti-fibrotic effects via inhibiting P38MAPK signaling in alcoholic cardiomyopathy both in vitro and in vivo. Our findings highlighted that LOX-1 could become a potential therapeutic target in the treatment of alcoholic cardiomyopathy. Graphical Abstract: uf0001